2020
DOI: 10.1177/2158244020927035
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religiosity on Fashion Store Patronage Intention of Muslim Consumers in Indonesia

Abstract: Religiosity covers all aspects of human life values. Consumer decision-making in Muslim product purchase needs to involve religiosity. Muslim fashion is increasingly popular and becomes a potential business for fashion entrepreneurs in Indonesia. This condition evokes a dilemma for the consumers as Muslim fashion users on whether they have to conform to the religious sharia or follow the trend. The purpose of this article is to identify the role of religiosity as a factor affecting Muslim consumers to revisit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 78 publications
1
12
0
2
Order By: Relevance
“…This indicates that the higher the students 'religiosity, the higher the students' perceived value towards Islamic Higher Education. Empirically, the results of this study are in line with the results of research conducted by Kusumawati et al (2020) which states that religiosity has a positive effect on customer perceived value.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This indicates that the higher the students 'religiosity, the higher the students' perceived value towards Islamic Higher Education. Empirically, the results of this study are in line with the results of research conducted by Kusumawati et al (2020) which states that religiosity has a positive effect on customer perceived value.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies explain that there is a relationship between religiosity with perceived value and consumer decisions. Research conducted by Kusumawati, et al (2020) found that religiosity has a positive impact on customer perceived value. Furthermore, Sardiana and Sari (2019) found results in their research which stated that religiosity has a positive effect on purchase intention.…”
Section: Religiositymentioning
confidence: 99%
“…Religiosity shows the extent to which someone is involved in their religion and the extent to which someone integrates religion or refers to transcendence in their daily lives (Saroglou, 2010). El-Menouar (2014), Ghorbani et al (2014), Kusumawati et al (2020), Mahudin et al (2016), and Olufadi (2017) has developed a measurement of Muslim religiosity but with a different approach.…”
Section: Religiositymentioning
confidence: 99%
“…There are around 85% of Muslims in the population of Indonesia. They have an increasing awareness of Muslim fashion following the fashion trends sponsored by public figures (Kusumawati et al, 2020). Also, religion is the heart of Indonesian people's lives, so religious practices are not only related to individuals but also to the business, political and social environment.…”
Section: Introductionmentioning
confidence: 99%